The Current State of Personnel Administration of Souphanouvong University: https://doi.org/10.69692/SUJMRD1001214 - VONGSOUANTHAM, Bounthieng; SOUKHAVONG, Sithane; VONGKHAMCHANH, Sounieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The main purpose of this research was to investigate the current state of personnel administration at Souphanouvong University. The descriptive survey method was employed in this study to collect the data from the sample group. The population included administrators, staff and teachers at Souphanouvong University with a total number of 415 people. The sample group was selected by using a purposive sampling method with a total number of 324 participants. The instrument used for data collection is the 5-likert-scale questionnaire which was validated by five experts in the area and then tested for reliability with the value of 0.979. The data were analyzed to find percentage, mean, and standard deviation. The findings reveal that the state of the personnel administration at Souphanouvong University was at the high level with a mean of 3.38 and standard deviation of 0.54 (= 3.83, S.D = 0.54). When considering each aspect, it was found to be practiced at a high level with a mean range from 3.60 to 3.97. The most practiced aspect is staff employment and management (= 3.97, S.D = 0.60), followed by the selection process (= 3.96, S.D = 0.65) and development ( = 3.95, S.D = 0.63) and the retirement from government officials (= 3.95, S.D = 0.65) respectively.